A minimum knapsack-based resource allocation for underlaying device-to-device communication. (2018) - Islam, Mohammad Tauhidul; Taha, Abd-Elhamid M.; Akl, Selim
As the numbers of smart devices increases, proximity-based services have enabled device-to-device (D2D) communication to be regarded as one of the major communication paradigms. In underlaying D2D, the devices communicating with each other directly use shared cellular resources. In this paper we propose a minimum knapsack-based interference aware resource allocation algorithm (MIKIRA) for D2D communication underlaying cellular networks. We compare the system sum rates, interference and signal-to-interference-and-noise-ratios (SINR) of MIKIRA with a graph-based resource allocation (GRA) algorithm and random allocation. In our three different sets of experiments with different percentages of D2D pairs in the total number of cellular users in the network, we observe that MIKIRA performs better than the other algorithms in terms of interference and SINR, and obtains a similar system sum rate. MIKIRA ( O ( n 2 log( n ))) is also computationally more efficient when compared with the GRA ( O ( n 3 )), which makes it suitable for use in the LTE scheduling period of 1 ms.